73.0k views
2 votes
1/3(c+1)=1/6(3c-5) explain & show steps!

User Kindrobot
by
5.4k points

1 Answer

2 votes
1. simplify 1/3 ( c + 1 ) to c + 1/3 ( c + 1 over 3 = 1/6 (3c - 5)

2. simplify 1/6 (3c - 5) to 3c - 5 over 6 ( c + 1 over 3 = 3c - 5 over 6 )

3. multiply both sides by 6 [The LCM of 3, 6] 2(c + 1) = 3c - 5

4. expand (2c + 2 = 3c - 5)

5. subtract 2c from both sides (2 = 3c - 5 - 2c)

6. simplify 3c - 5 - 2c to c - 5 (2 = c - 5)

7. add 5 to both sides (2 + 5 = c)

8. simplify 2 + 5 to 7 (7 = c)

9. switch sides (c = 7 )

so in conclusion the answer is 7.



User Svinota
by
6.1k points